Constitucional Guarantees - Ferrero Rebagliati, Raúl (1969)
This paper offers an approach to constitutional guarantees in the Peruvian legal system. According to the author, constitutional guarantees, unlike national guarantees, must be understood as those protection mechanisms that allow the holder of a subjective public right to go to court for the protection of the violated or threatened right, either by the state or by an individual. In this context, the analysis focuses mainly on the classification of said mechanisms of jurisdictional protection of human rights, within which habeas corpus, Amparo, unconstitutionality action, and popular action are analyzed.